Purification of an exopolygalacturonase from Penicillium viridicatum RFC3 produced in submerged fermentation - Gomes, Eleni [UNESP] (2009)
An exo-PG obtained from Penicillium viridicatum in submerged fermentation was purified to homogeneity. The apparent molecular weight of the enzyme was 92 kDa, optimum pH and temperature for activity were pH 5 and 50-55°C. The exo-PG showed a profile of an exo-polygalacturonase, releasing galacturonic acid by hydrolysis of pectin with a high degree of esterification (D.E.). Ions Ca 2+ enhanced the stability of enzyme and its activity by 30%. The K m was 1.30 in absence of Ca 2+ and 1.16mg mL -1 in presence of this ion. In relation to the Vmax the presence of this ion increased from 1.76 to 2.07 μmol min -1mg -1. Copyright © 2009 Eleni Gomes et al.